Additive Manufacturing and Injection Moulding of High-Performance IF-WS2/PEEK Nanocomposites: A Comparative Study - Golbang, Atefeh; Mokhtari, Mozaffar; Harkin-Jones, Eileen; Archer, Edward; Mcilhagger, Alistair (Frontiers in Materials, 2021)
In this study, PEEK nanocomposites with 0, 0.5, 1 and 2wt% IF-WS2 were manufactured by injection moulding and Fused Deposition Modelling (FDM). To compare the impact of the two processing methods and the incorporated nanoparticles on the morphology, crystallization and final mechanical properties of the nanocomposites, SEM, DSC and tensile testing were performed. In general, a good distribution of nanoparticles was observed in PEEK, although larger agglomerates were visible at 2 wt% IF-WS2. The crystallization degree of PEEK increased with increasing loading of IF-WS2 nanoparticles up to 1wt% and then declined at 2wt%, due to lower level of particle dispersion in this sample. The 3D printed samples showed slightly higher crystallinity at each IF-WS2 loading in relation to the injection moulded samples and extruded filaments, because of multiple reheating effect from subsequent layer deposition during FDM, causing recrystallization. In general, incorporation of IF-WS2 nanoparticles increased the mechanical properties of pure PEEK in both 3D printed and injection moulded samples. However, this increment was more noticeable in the 3D-printed nanocomposite samples, resulting in smaller gap between the mechanical properties of the 3D-printed samples and the injection moulded counterparts, in respect to pure PEEK, particularly at 1wt% IF-WS2. This effect is ascribed to the increased inter-layer bonding of PEEK in the presence of IF-WS2 nanoparticles in FDM. In general, the lower mechanical properties of the 3D printed samples compared with the injection moulded ones are ascribed to poor interlayer bonding between the deposited layers and the presence of voids. However, addition of just 1 wt% of IF-WS2 nanoparticles into PEEK increased the tensile strength and Young’s modulus of the FDM PEEK materials to similar levels to those achieved for unfilled injection moulded PEEK. Therefore, incorporation of IF-WS2 nanoparticles into PEEK is a useful strategy to improve the mechanical performance of FDM PEEK.